DANIġTAY GERÇEKTEN150 YAġINDA MI?(*)84 Sayılı Kanun’un Geçici Maddesinin Anlam veKapsamı Üzerine Bir Ġnceleme - (:unkn) unknown (My University, 2020)
Bu çalıĢmada, DanıĢtay‟ın köklü tarihini konu almıĢ eserlerde aralanmamıĢ,belki de “unut(tur)ulmuĢ” tarihsel tekil olguya ve bu olgu üzerinden “DanıĢtay 150yaĢında mıdır?” Ģeklinde spekülatif atakla kurumsal süreklilik tezine dikkat çekmekamaçlanmıĢtır. 27 Mayıs müdahalesinin ardından çıkartılan 84 sayılı Kanunun geçicimaddesiyle DanıĢtay üye kadrolarının yaklaĢık dörtte üçü emekliye sevk edilerek zımnen “ilga” edilmiĢ ve ekli liste ile kurum yeniden “ihdas” edilmiĢtir. Bu çalıĢmada “açkapa” Ģeklindeki bu müdahalenin mahiyeti, “ilga” ve “ihdas” kavramları üzerindenirdelenerek; unsurlarıyla birlikte “tespit” edilen bu vakıanın kurumsal süreklilikten“resmi bir kopuĢu” temsil etmediği; aksine diyakronik bir süreklilikte yalnızca bir “kesinti” olarak değerlendirilmesi gerektiği iddia edilecektir.

This paper aims to underline a phenomenon which has not been analyzed or may not have been referred “deliberately” in the literature about the history of the Council of State, and thus to point out the argument of continuity by raising the assertion of “the Council of State is the 150-year-old institution”. The phenomenon is that upon the 1960 Turkish coup d‟état, the provisional article of the Act No.84 tacitly abrogated approximately three-quarters of judges and reintroduced by the Act attachment. The nature of this intervention is characterized as “cut-and-cover” and is stated under the terms of “abrogation” and “formation”. It is claimed that this contingency may not be evaluated as discontinuity, but rather may be called as “an interruption” in a diachronic consistency of the Council of State.
IS THE COUNCIL OF STATE A 150-YEAR-OLD INSTITUTION? The Nature of the Provisional Article of the Act No. 84